Al-Anashir Al-Dakhiliyah Fi Qishash Musa wa Yusuf Alaihis Salam Fi Al-Qur’an al-Karim: Dirasah Muqaranah - Nuril Aiddatul Izzah (Arabic Language and Letters Department, 2020)
The purpose of this study was to find the intrinsic elements and the comparison of the intrinsic elements between story of the prophet Musa a.s and the prophet Yusuf a.s in surah al-qosos and surah yusuf in the Qur’an.Both have almost the same life journey. The story of prophet Musa a.s is recorded in various surahs and the story of prophet yusuf a.s is recorded in only one surah. This research examines the story of prophet Musa a.s in surah al-qosos verses 1-70 and the story of prophet Yusuf a.s in surah yusuf verses 1-111. This study used a qualitative descriptive method using data in the form of dialogue texts and monologues in the surah al-qosos and surah yusuf which showed the intrinsic elements and the comparison of the intrinsic elements. Intrinsic elements and comparison of the intrinsic elements studied include characterization,plot,setting,theme and language style. The result of this study are the intrinsic elements of the story prophet Musa a.s and Yusuf a.s and the comparison of the intrinsic element of the two stories.